Variation of Particulate Matter (PM10) in a Semi-urban Area during 2015 Malaysia Haze - Bahiyah Abd Wahid, Nurul; Abdul Razak, Helmiah; Adawiyah Amzah, Rabieatul (International Journal of Engineering and Technology, 2018)
Particulate matter (PM10) is one of the most dangerous air pollutants released during haze phenomena which can disrupt lung function, circulatory system and reduce visibility. The aims of this study were to determine the trend of PM10 in Tanjung Malim, Perak during 2015 haze episode. The four months trend of PM10 was analyzed, along with daily trend for the highest concentration of PM10 recorded during the haze episode. In addition, the correlation between PM10 and meteorological parameters, such as wind speed, temperature, and humidity were also analyzed. Result indicated that, PM10 level during September and October 2015, have mostly exceeded the Recommended Malaysian Air Quality Guidelines (RMAQG) by Malaysian Government (150 μg/m3). From the 72h backward trajectories, it can be stated that most of the pollutants came from biomass burning in neighbouring country, during the southwest monsoon. Changes in PM10 concentration were possibly influenced by meteorological factors which play an important role in haze episode.